Desempenho, características da carcaça e qualidade da carne de bovinos Nelore em sistemas integrados de produção - Cordeiro, Poliana Oliveira (2019)
The aim of this study was to evaluate the body characteristics of Nellore steers in Integrated Production Systems: Crop-Livestock (ICL); Livestock-Forestry (ILF), Crop-LivestockForestry (ICLF) and Livestock (L). A complete randomized block design with four replicates each was used. Forty-eight Nellore steers with mean initial weight of 272 ± 11 kg and mean age of 18 ± 3 months were included in the study in Braquiaria pasture (Urochloa brizantha) cv. Marandu. The morphometric measurements were taken every 56 days: body height, rump height, body length, back-loin length, rump width and the thoracic perimeter of the animals, and measurements of ribeye area, backfat thickness and rump fat thickness by ultrasound. The morphometric characteristics of the height of the withers (p = 0.1966), croup height (p = 0.0762), body length (p = 0.9769), dorsum-loin length (p = 0.983), width of the rump (p = 0.3832) and thoracic perimeter (p = 0.0684), did not present significant differences caused by the production systems P, ILP, IPF and ILPF. When evaluating the significant correlation between the weight of the steers and the morphometric measurements, high magnitude coefficients were found (r = 0.71 to 0.95), and the weight and thoracic perimeter (r = 0.95) were the most correlated. Body measurements of Nellore steers were not affected by the integrated ILP, IPF, ILPF and P systems. However, the evaluation of body growth by means of morphometric and ultrasound gauging together facilitates the understanding of animal growth.